Performa pada Motor Bakar 6-Langkah dengan Langkah Power Ekspansi sampai Titik Mati Bawah - Sepriyatno, Riswan; Siswanto, Eko; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2021)
This study aims are to observe the performance of a six-stroke combustion motor and to analyze the thermodynamics of a six-stroke combustion engine with a power expansion step to the bottom dead center. The fuel used in this observation is pertalite with a RON 90 value. The method used is a true experimental method, with independent variables, namely 35%, 40%, 45%, and 50% throttle openings with loading on the prony disc brake of 10 kg, 20kg, 30kg, 40kg, and 50kg. In the torque data, each throttle opening shows the highest number of 7.26 (Nm) with a load of 50kg and the lowest value of 2.01 (Nm) with a load of 10kg, for effective power the highest value is 8.47 (kW) at 50% throttle opening with load is 40kg and the lowest value is 2.49 (kW) at 35% throttle opening with a load of 10kg, while for the specific fuel consumption (SFC) the highest value is 4.28 (kg/Hp.h) at 40% throttle opening with a load of 10kg and the lowest value is 0.77 (kg/Hp.h) at 50% throttle openings with a load of 50kg, and for the thermal efficiency of the six-stroke motor, which means an average increase of 14.58% compared to the thermal efficiency of the conventional 4-stroke internal combustion engine.